DETERMINATION OF ECONOMIC GROWTH IN NORTH SUMATRA PROVINCE - Uli Amsyah; Amirullah; Tsabitha Dwitanahd; Nazwa Hafyuna br Nasution; Inggrita Gusti Sari Nasution (Universitas Efarina, 2023)
This study aims to find out how the influence of the Economic Development Index, Poverty, Unemployment, Capital Expenditure, Total Capital and Labor partially or simultaneously on Economic Growth by taking case studies in North Sumatra Province. The type of research used is descriptive quantitative, namely a descriptive approach with a quantitative approach. The data used is secondary data, this research is panel data research with panel data regression analysis method conducted with Eviews 12.0. The results of this study indicate that the HDI variable has a significantly positive effect on Economic Growth, Poverty has a negative but insignificant effect on Economic Growth, Unemployment has a positive but insignificant effect on Economic Growth, Capital Expenditure has a negative but insignificant effect on Economic Growth, Total Population has a negative but insignificant effect on Economic Growth and Labor has a significantly positive effect on Economic Growth.